Smiling doctor, satisfied patient—the impact of facial expressions on doctor-patient interactions - Schneider, Pia; Zerbini, Giulia; Reicherts, Philipp; Reicherts, Miriam; Roob, Nina; Hallmen, Tobias; André, Elisabeth; Rotthoff, Thomas; Kunz, Miriam (Frontiers in Medicine, 2025)
IntroductionAlthough the importance of facial expressions for good doctor-patient communication is widely acknowledged, empirical evidence supporting this notion is scarce. We used a fine-grained, anatomically-based measure to investigate which facial expressions are displayed in (simulated) doctor-patient consultations and whether these can predict communication quality.MethodsFifty two medical students engaged in simulated doctor-patient consultations with standardized patients (SPs) and their facial expressions were analyzed using the Facial-Action-Coding-System (FACS). The quality of the communication was rated by SPs, medical students, and by communication experts. SPs also rated their level of comfort.ResultsThe predominant facial expression being displayed by medical students was smiling. Medical students' smiling positively predicted the communication quality and level of comfort experienced by SPs. In contrast, smiling had little effect on medical students' self- and expert-assessments of communication quality. Smiling of medical students significantly predicted patient level of comfort and perceived quality of communication. This predictive power was found for genuine and for social smiles as well as for smiles displayed during speaking and during listening.DiscussionSmiling seems to be a robust non-verbal behavior that has the potential to improve doctor-patient communication. This knowledge should be taken into consideration in medical training programs.